Decentralization in International Relations: A Study of Semarang City's Paradiplomacy - Hermini Susiatiningsih; Nadia Farabi; Satwika Paramasatya; Sheiffi Puspapertiwi (E3S Web of Conferences, 2018)
Democratization in developing countries triggered by globalization has led decentralization. Post New-Order Indonesia chose decentralization as its policy to improve democratization, allowing transfer of authority to its local governments, thus raises roles taken by sub-state actors, including in international relations. States, regions, provinces and cities seek their way to promote trade, investments, cooperation, and in some cases, political support, through cross-borders contacts with their international counterparts. The phenomenon which later understood as “paradiplomacy” is thus defined as communication conducted by sub-state actors aimed to promote identity and or pursuing local interests. This study analyze how Semarang, as a melting pot city in Java, positioned itself in international community and develop its own paradiplomacy. The study finds that Municipal Government of Semarang with authority expanded by decentralization uses paradiplomacy as a mean to achieve economic interest, especially to expand market and attract foreign investment, with its environmental issue that remains left-behind. The prototype of paradiplomacy is found in “SemBiz”, annual expo in trade and investment held by Municipal Government of Semarang. Not only serves economic development in Semarang, paradiplomacy is also utilized to preserve, if not strengthen, its locality as integral part of Semarang's identity.